The philosophers and the Bible the debate on sacred scripture on early modern thought - International Conference "I filosofi e la Bibbia: Letture filosofiche delle Scritture in età moderna" 2019 Rom; Viterbo; Del Prete, Antonella 1967-; Schino, Anna Lisa 1953-; Totaro, Pina; Università degli studi della Tuscia Dipartimento di studi linguistico-letterari, storico-filosofici e giuridici; Università degli studi di Roma "La Sapienza" Dipartimento di Filosofia; Istituto lessico intellettuale europeo e storia delle idee (Leiden Boston Brill, 2022)
"The Bible is the breeding ground for the issues nourishing philosophy during the Early Modern age. Different conceptions of God, the world, and the human being have been shaped based on the history of salvation, constructed (or deconstructed) in relation to the various approaches and readings of the Holy Scriptures. This book aims at inquiring the different uses that philosophers made of the Bible. The essays collected in it provide a new perspective on the subject, overcoming the traditional opposition "faith versus science" and enhancing the philosophical approach to the Sacred Scriptures. Philosophers thus promoted a universally recognized moral message and forged the conceptions of the nature, of politics, and of the human being proper to the Early Modern age"--
"Papers presented during the international conference I filosofi e la Bibbia: Letture filosofiche delle Scritture in età moderna, which took place in Rome and Viterbo on 9-10 May 2019 and was organized by the Department for Linguistic, Literary, and Historical Studies (DISTU) of the University of Tuscia, the Department of Philosophy of "La Sapienza" University in Rome, and the National Research Council's Institute for the European Intellectual Lexicon and History of Ideas (ILIESI-CNR) in Rome"--Introduction
Includes bibliographical references and index
Keywords: Bible -- Philosophy -- Congresses; Bible -- Criticism, interpretation, etc -- Congresses; Bible -- Use -- Congresses; Philosophy, Modern; Konferenzschrift